Impacts of the leadership and the communication social among the personnel of cleaning public of governments local peruvian in times of the COVID-19 - Narro Ortiz, José Luis (2024)
Objective. The study sought determine how the leadership and the communication social influenced in the performance job of the workers of cleaning public in governments local of the Peru during the pandemic by the COVID-19. Methods. It used the identification of articles that involve to the variables leadership, job performance and social communication, giving importance to those published from 2020 to 2024. The criteria of selection oriented to those works that contributed to the knowledge of the leadership, allowing verified besides the performance and the importance of the communication. The methodology used were the analysis of the discourse and the review bibliographic of the theory grounded, belonging to the paradigm interpretive. Results. It evidenced the leadership during the pandemic, since the performance job it was a consequence natural of the commitment of the workers' and the communication social informed with maturity and responsibility. Conclusions. The communication social was important during the pandemic, showing different types of leadership and influencing about the performance job in workers of cleaning public of governments local.